Cadastral survey of unique landscape features via the examples of Vászoly, Hungary - Tóth, Szilvia; Endrődi, Judit; Horvát, Gergely (Acta Geographica Debrecina Landscape & Environment series, 2014)
In the Hungarian legal system the Act on Nature Conservation contains a peculiar category, the notion of the unique landscape feature. The unique landscape feature is a natural or man-made object which represents value for local people. The purpose of this study is on the one hand to familiarize this specific category, on the other hand to introduce the method of cadastral survey via the example of a small Hungarian settlement, Vászoly. Vászoly and its surroundings are situated on the south-eastern part of the Balaton Uplands, a part of the Bakony Region. In spite of the survey, the distribution of the features among the categories reflects the national tendency, that is, most of the cadastred landscape features in Vászoly are cultural-historical ones, because these types of features are located mostly within the inner areas of the settlements, which makes them easier to survey. However, these features are not always really valuable. It can be stated that most of the features are related to the settlement (mostly features of sacral traditions) and agricultural production (first of all features of viniculture). Surveying the sets of the unique landscape features, the changing landscape patterns, the certain landscape characters and the peculiarities of the landscape explain their origin and former function.